EVALUASI EKOTURISME DI TAMAN NASIONAL GUNUNG CIREMAI - Ichwan Muslih; Tutut Sunarminto; Ricky Avenzora (Media Konservasi, 2011)
As a new nature preservation area in West Java, the Gunung Ciremai National Park still need much supports to reach its optimum function; including ecotourism activities. Therefore, an ecotourism resource evaluation had been done in order to identify its ecotourism potentials. Amongst so many ecotourism objects in this area, the Elang Jawa (Spizateus bartelsi), Orchidae and the Situ Sangiang (Lake Sangiang) had the highest value for ecotourism attractions due to the criteria and indicators that were applied in the assessment. Further, in term of management perspectives, the research found that the circulation facilities in the area had become the most crucial problem for visitors to access and enjoy many ecotourism resources in the national park. Keywords: national park, ecotourism, ecotourism resources evaluation